PERBANDINGAN PARAMETER DESAIN DAN PARAMETER OPERASI BEBERAPA KALSINER PABRIK SEMEN DI INDONESIA - Darmanto, Prihadi Setyo (Mesin, 2006)
Cement calsiner is a reactor where the decarbonization of lime stone and fuel combustion processes take place simultaneously. Decarbonization of lime stone is endothermic process and uses the heat produced by the combustion of fuel. However, because these two simultaneous processes produce CO2, the effectiveness of both processes depend on the CO2 concentration along the gas stream inside the calciner. The complexity of these simultaneous processes causes the variation of calciner design that could be found in cement industry. Especially for the calciner using coal as a fuel, this variation design influences significantly to the operation of the calciner. This paper presents a comparison study of design and operational parameters of some calciners in Indonesian cement manufacturers. The result of study could be used for designers to consider some principal parameters during design process so that the calciner could operate properly and give a better performance.